2002
DOI: 10.1159/000066173
|View full text |Cite
|
Sign up to set email alerts
|

Transient Topographical Disorientation

Abstract: Transient topographical disorientation (TTD) is a short-lasting inability to find one’s way in a familiar environment, while the patient remains conscious and is able to recall what happened. We report the study of 10 patients with episodes of TTD, studied on the days following the last episode. The episodes of TTD could be separated into two types: the patients either reported difficulties in spatial orientation with preserved abilities to recognize landmarks and objects, or the difficulties appeared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…Recently, cases of TDD of unknown etiology have been reported [10, 11], and some of them were considered to be an epileptic manifestation [10], but vascular origin was not suggested for these cases. Our patients had vascular risk factors such as diabetes (case 1), hypertension (case 2), and atrial fibrillation (case 2).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cases of TDD of unknown etiology have been reported [10, 11], and some of them were considered to be an epileptic manifestation [10], but vascular origin was not suggested for these cases. Our patients had vascular risk factors such as diabetes (case 1), hypertension (case 2), and atrial fibrillation (case 2).…”
Section: Discussionmentioning
confidence: 99%
“…The selective deficit of topographical disorientation is relatively rare and has been attributed to cerebrovascular disease, Alzheimer's disease, and frontotemporal dementia [1][2][3]. Recently, cases of transient topographical amnesia (TTA) have been published [4][5][6][7]. These cases are characterized by a sudden onset and short-lasting disturbance in orientation without any loss of consciousness or episodic memory.…”
Section: Dear Sirsmentioning
confidence: 99%
“…Transient topographical amnesia is a rare symptom, and previous literature reported that some episodes are caused by transient ischemic attack [8], migraine [9], normal pressure hydrocephalus [10], and epilepsy [7,11]. The etiology of TTA remains unknown.…”
Section: Dear Sirsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional compensation of topographical disorientation in H.W. was rapid and complete, as reported in similar previous cases (Gil‐Néciga et al., 2002; Rivest, Svoboda, McCarthy, & Moscovitch, 2018). The complete recovery of an allocentric navigation strategy despite a residual hippocampal lesion in follow‐up MRI illustrates the great plasticity of the human navigation network (Byrne et al., 2007; Ekstrom et al., 2014).…”
Section: Introductionmentioning
confidence: 99%